Análisis del impacto socio económico de la afiliación obligatoria de las trabajadoras domésticas al Instituto Ecuatoriano de Seguridad Social en la ciudad de Loja en el año 2012 - Cueva Agurto, Leidy Diana (2016)
In developing research housework analyzed the socio-economic impact of affiliation to the Ecuadorian Institute of Social Security of domestic workers, social security, social benefits to which they have access, basic pay, reserve funds, thirteenth and fourteenth compensation, vacation, undervaluation of domestic work, domestic work in and live-out, hiring part-time or part-time domestic workers. This research aimed to determine the positive and negative socioeconomic effects produced compulsory membership to the Ecuadorian Institute of Social Security of domestic workers, the problems affecting the sector was identified as their work is not valued by employers their pay is not set by law, not their work schedules are respected, and also not affiliated to social security. Methods, analytical, deductive, and techniques such as bibliography was used, the interview that was conducted by Dr. Carlos Bustamante Director of Membership and Employer Control IESS, the survey was applied to the 338 domestic workers. Finally it is concluded that economic partner affiliation IESS domestic workers, effects positive is that by being members can access the benefits of social security this is a step to be recognized as other workers, the negatives are that employers are undervalued domestic work and are not fulfilling the rights of these women workers.